VD_FINDINFO HC / 2016 / 160 vom 29. Januar 2016 - VD Tribunal cantonal (2016)
BAIL À LOYER, EXPULSION DE LOCATAIRE, CAS CLAIR, COMPENSATION DE CRÉANCES, DEMEURE, SOMMATION | 257d CO, 257 CPC (CH), 312 al. 1 CPC (CH)